Video Self Modelling untuk Mengatasi Kecemasan Berbicara di Depan Umum pada Mahasiswa di Makassar - A.Diva Zalzabilah E.Pabokori; Kurniati Zainuddin; Ahmad Ridfah (Departement of Mathematics Education, 2023)
Public speaking is an important means of conveying messages, information, and ideas that every student has. However, until now there are still students who have difficulty speaking in public to explain their ideas to others. This study aims to examine the effectiveness of video self-modeling in overcoming public speaking anxiety in university students in Makassar City. This study used a one-group pretest-posttest experimental design. The subjects in this study were 8 students who had public speaking anxiety. The measuring instrument used in this study is a public speaking anxiety scale. The data analysis technique used was the Wilcoxon Test. The results showed that video self-modeling is effective in overcoming public speaking anxiety in college students in Makassar City (ρ=0.014). The implication of this research is that video self-modeling can be used as a method to reduce public speaking anxiety.